Perbandingan Pendekatan Computer Science Unplugged dan Plugged-In Learning pada Pembelajaran Informatika - Prameswara, Irvan; Pramudita, Dias Aziz (Universitas Hamzanwadi, 2024)
Currently, informatics learning at Al-Islam Abidin Junior High School in Surakarta is often faced with the challenge of choosing effective and interesting learning methods for students, so that it causes teachers and students to find it difficult to determine which methods are more suitable to be applied in the classroom. There are several kinds of approaches to learning in informatics subject matter, namely by using CS unplugged and plugged-in learning. This study aims to analyze the comparison of CS unplugged and plugged-in learning approaches applied at Al-Islam Abidin Junior High School in Surakarta. The method used in this study is to use a quantitative approach. The participants involved totaled 40 people who would be divided into 2 classes, namely the control class and the experimental class, each class consisting of 20 people. Data collection in this study used pre-test and post-test. The results of pre-test and post-test testing show that learning using computer media (plugged learning) gets higher scores so it can be concluded that the plugged learning method is more suitable for use in informatics subjects. The impact of plugged-in learning method is that students can play and learn using technology, meanwhile unplugged learning makes the student can learn dependence on technology.